United Nations Multidimensional Integrated Stabilization Mission in Mali - Korecki, Zbyšek (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The security and political instability of West and Central African countries is influenced by several factors and is a topical issue for the United Nations (UN) and the European Union’s (EU) foreign policy. The security of the region decreased to a low level after the declaration of the war on terrorism in 2003. According to the Global Peace Index (GPI), which takes into account the militarization and security of society, countries such as Mali (2.686 — 144), Central African Republic (3.236 — 155) or Libya (3.262 — 157) compared to other countries of the world have long been in the unflattering index position, which is evaluated by 163 countries. The destabilization of Libya and the consequences of the fall of the dictatorial regime of Muammar Gaddafiled to the subsequent spread of instability in the region in 2011. After the emergence of the radical organization of the Islamic State (IS), as well as other organized armed groups in the Middle East and in some African Union states, fighters are rapidly expanding into Mali, Mauritania and Niger. The UN Multidimensional Integrated Stabilization Mission in Mali (MINUSMA) was launched in July 2013. As asymmetric terrorist attacks on UN peacekeepers have increased, a UN-level debate was held to strengthen the mandate and capabilities of UN MINUSMA. Contributing countries of the African Union were aware of the fact that terrorist attacks could spread to neighboring countries and therefore called on UN Member States to become more actively involved in the mission in Mali. The pre-sented article analyzes the political and security situation of Mali and the participation of members of the Army of the Czech Republic at the UN MINUSMA. The author of the article concluded that Mali in the post-conflict reconstruction needs to implement all stages of post-conflict reconstruction and necessarily needs the presence of UN and EU troops.Participation of members of the Army of the Czech Republic should correspond to the ambitions of the Czech Republic within the EU in achieving the objectives of stabilizing the unstable territories in the neighborhood in order to prevent future potential security risks.Pobierz artykuł
Keywords: odbudowa pokonfliktowa; terroryzm; misja pokojowa; dżihad